PEMANFAATAN KITIN I KITOSAN SEBAGAI BAHAN ANTI MIKROBA - R. Sarwono (Research Center for Chemistry - LIPI, 2010)
Chitin is a natural polymer which consists in the living thing such as shrimp, crabs, lobsters, yeast, insect and fungi. Chitin is usually produced fromshellfish such as shrimp shell, crabs, lobsters. They are demineralization of crustacean using strong acid OT base. Deacetilization of chitin using strong base and heating gave chitosan. Chitosan has many application such as food preservation, anti microbial, water treatment, anti oxidation, and fat absorption. Anti microbial products such as sport dressing, hand globt;linen, and anti virus and antracnose of red chili pepper. Anti bacterial of chitosan come from the amine functional group, that strong positive charge. Membrane of cell has negative charge. Interaction between positive and negative charge resulted membrane permeable suffer osmotic pressure which affect to the equilibrium inside the cell, it may cause theinhibition the growth of the microorganisms. There is also hydrolysis occurs to the cellwall that may cause the leak of electrolyte from the cell, it may cause the cell becomedead.Key words : crustacean waste, chitin, chitosan, anti bacterial